ITDC DAN NARASI BARU PARIWISATA LOMBOK MENGEMAS PESONA LOKAL DENGAN SENTUHAN KELAS DUNIA - Riyanti, Anti; Lisdiani, Azkiya; Agiyanti, Dwi; Nugroho, Bayu; Yanti Fitriana, Liani (Puslitabmas Batam Tourism Polytecnic, 2025)
This article aims to describe ITDC's new strategy in packaging Lombok's local charm with a world- class touch. The main focus is on infrastructure development, especially Mandalika. This research also explains how ITDC has succeeded in packaging the local charm of Lombok into world-class tourism products such as the local values raised, the target market, and the communication strategies used. The findings of the study show that the new narrative of Lombok tourism has succeeded in creating a unique destination image and attracting international tourists. Because the local party, the private sector, and the government jointly build and manage tourism well in Lombok. Based on data and descriptive qualitative analysis, a new tourism development strategy based on nature and culture that is a regional attraction in the Kuta Mandalika Lombok tourist attraction.